Swimmer’s Ear: A Case Report and Literature Review - Amanda Muhamad Bauzir; Arsiyoga Bimo Fadhyki; Muhammad Hanun Mahyuddin; Ulaa Haniifah (Asian Australasian Neuro and Health Science Journal (AANHS-J), 2022)
Introduction: Otitis externa (OE) Circumcrypt is an inflammation accompanied by furuncle growth in the outer ear with or without infection. Circumcrypt OE events are identified with swimmers or other names Swimmer’s Ear, because their ears are moist. Circumcrypt OE cases can be distinguished based on the duration of action, namely acute or chronic. Case Reports: A 21-year-old male patient came with complaints of pain in the ear, previously the patient also felt a feeling of fullness in the ear. Previously the patient had a history of swimming and cleaning the ears afterwards. Another complaint is decreased hearing and yellow discharge from the left ear. Conclusion: Otitis externa (OE) Circumcrypt or Swimmer’s Ear is an inflammation of the ear caused by bacteria, fungi or their groups that grow in moist places. To make a diagnosis through anamnesis, local status examination and support. OE management can be done with pharmacology and Spooling measures to clean the ear.